Brazilian practice guidelines for stroke rehabilitation: part II - Minelli, Cesar (2022)
The Brazilian Practice Guidelines for Stroke Rehabilitation - Part II, developed by the Scientific Department of Neurological Rehabilitation of the Brazilian Academy of Neurology (Academia Brasileira de Neurologia, in Portuguese), focuses on specific rehabilitation techniques to aid recovery from impairment and disability after stroke. As in Part I, Part II is also based on recently available evidence from randomized controlled trials, systematic reviews, meta-analyses, and other guidelines. Part II covers disorders of communication, dysphagia, postural control and balance, ataxias, spasticity, upper limb rehabilitation, gait, cognition, unilateral spatial neglect, sensory impairments, home rehabilitation, medication adherence, palliative care, cerebrovascular events related to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, the future of stroke rehabilitation, and stroke websites to support patients and caregivers. Our goal is to provide health professionals with more recent knowledge and recommendations for better rehabilitation care after stroke.